2015
DOI: 10.1097/pec.0000000000000427
|View full text |Cite
|
Sign up to set email alerts
|

“Bucking” for a Diagnosis

Abstract: Foreign body ingestions are all too common in children. The adverse effects of many of these ingestions are well known. We present an interesting case report of "Buckyballs" and the implications of ingesting or placing in other orifices these strong rare-earth magnets. We illustrate that these toys can be of possible disastrous consequences. Although these products were removed from the marketplace, there is still the possibility of negative consequences. Our aim was to inform the physician population of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Delicate manipulation is essential, while excessive force may lead to a risk of gut perforation and leak ( 28 , 29 ). If the time since ingestion is >12 h and Buckyballs are suspected to have passed through the pylorus into the small bowel, a series of abdominal radiography is needed ( 30 , 31 ), and surgical intervention should be considered in those who present symptoms and signs of acute abdomen. Laparoscopic surgery is an ideal approach depending on an experienced surgeon team and available facilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delicate manipulation is essential, while excessive force may lead to a risk of gut perforation and leak ( 28 , 29 ). If the time since ingestion is >12 h and Buckyballs are suspected to have passed through the pylorus into the small bowel, a series of abdominal radiography is needed ( 30 , 31 ), and surgical intervention should be considered in those who present symptoms and signs of acute abdomen. Laparoscopic surgery is an ideal approach depending on an experienced surgeon team and available facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion of multiple high-powered Buckyballs in children may lead to a high risk of severe gastrointestinal injuries, which need prompt decision-making and surgical intervention ( 30 ). In unwitnessed cases, a vague medical history and presentation of nonspecific symptoms often make the diagnosis difficult.…”
Section: Discussionmentioning
confidence: 99%
“…[1] The children's toy known as "Buckyballs" is spherical fullerene molecules with C 60 formula made of 20 hexagons and 12 pentagons with a carbon atom at each vertex. [2] These and similar rare earth metals are have been made into magnetic children's toys and are 5-10 times stronger than traditional magnets. [2] Ingestion of these toy magnetic balls has been associated with serious gastrointestinal (GI) injuries requiring emergent surgical interventions such as laparoscopy or laparotomy, GI perforation, fistula formation, and death in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…[2] These and similar rare earth metals are have been made into magnetic children's toys and are 5-10 times stronger than traditional magnets. [2] Ingestion of these toy magnetic balls has been associated with serious gastrointestinal (GI) injuries requiring emergent surgical interventions such as laparoscopy or laparotomy, GI perforation, fistula formation, and death in some cases. [1][2][3][4] Reviews of studies that discuss multiple magnet ingestions have reported successful endoscopic removal of up to ingestion of 27 magnets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation